2020
DOI: 10.1063/5.0003616
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic shear and the intrinsic conformal geometry of null-infinity

Abstract: In this article, we propose a new geometrization of the radiative phase space of asymptotically flat space-times: we show that the geometry induced on null-infinity by the presence of gravitational waves can be understood to be a generalization of the tractor calculus of conformal manifolds adapted to the case of degenerate conformal metrics. It follows that the whole formalism is, by construction, manifestly conformally invariant. We first show that a choice of asymptotic shear amounts to a choice of linear d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(70 citation statements)
references
References 82 publications
1
69
0
Order By: Relevance
“…Similarly, in the context of asymptotically flat spacetimes, letting flux going through null infinity is a necessary condition to consider radiating solutions. In this case, the asymptotic shear C AB plays the role of source and the charges are non-integrable [23,24,31,112]. When asymptotically locally flat spacetimes are considered, the transverse boundary metric q AB also plays the role of source [30,49,50,58,124].…”
Section: Jhep05(2021)210 6 Commentsmentioning
confidence: 99%
“…Similarly, in the context of asymptotically flat spacetimes, letting flux going through null infinity is a necessary condition to consider radiating solutions. In this case, the asymptotic shear C AB plays the role of source and the charges are non-integrable [23,24,31,112]. When asymptotically locally flat spacetimes are considered, the transverse boundary metric q AB also plays the role of source [30,49,50,58,124].…”
Section: Jhep05(2021)210 6 Commentsmentioning
confidence: 99%
“…In the language of [70,71], this conformal extension means that the universal structure on I is reduced from a null vector and degenerate metric (original BMS) to a (thermal) Carroll structure (BMSW) [28,31,72,73]; see also [74,75] for an intrinsic and conformally invariant geometrical description of null infinity.…”
Section: Introductionmentioning
confidence: 99%
“…How are we, however, to interpret all this from the point of view of null-infinity, i.e from the point of view of the Carroll geometry? A hint of the solution is given by the recent work [20]. In this work, it was shown that a (d − 1)dimensional conformal Carroll geometry (n a , h ab , I ) (here bold notation is used to emphasised that the fields are weighted) is canonically associated to a (d+1)-dimensional vector bundle the "null-tractor bundle"…”
Section: Introductionmentioning
confidence: 97%
“…We now discuss precisely how this equivalence can arise. It was proven in [20] that any choice of trivialisation u : I → R for I → S d−1 canonically defines an isomorphism…”
Section: Introductionmentioning
confidence: 99%